2003
DOI: 10.1007/s10142-003-0094-6
|View full text |Cite
|
Sign up to set email alerts
|

Genes associated with the end of dormancy in grapes

Abstract: A grape bud EST library was constructed and 4270 ESTs sequenced. The library clones were arrayed for the purpose of investigating the level of gene expression over time, particularly leading up to the buds' release from dormancy. The arrays were hybridized with P(33)-labeled probes produced from samples of buds collected at weekly intervals. These probes covered the time from 9 weeks prior to bud burst until just after the emergence of the shoots. Expression patterns from these genes have been examined. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 8 publications
3
40
0
Order By: Relevance
“…These studies suggest involvement of regulation of gene expression, signaling mechanisms, cell to cell communication and cell cycle in dormancy release (Arora et al 2003;Pang et al 2007;Rohde and Bhalerao 2007). Few large-scale transcription proWling studies, using EST collections and microarrays, may shed light on additional candidate proteins and pathways that might be involved in the regulation and execution of bud dormancy release such as Lea proteins, GTP-binding proteins, Xavonoid biosynthesis and auxin signaling (Pacey-Miller et al 2003;Horvath et al 2005Horvath et al , 2006Keilin et al 2007;Mazzitelli et al 2007;Ruttink et al 2007). Further studies with well deWned experimental systems are needed for the identiWcation of the core cellular processes that are connected with dormancy release.…”
Section: Introductionmentioning
confidence: 95%
“…These studies suggest involvement of regulation of gene expression, signaling mechanisms, cell to cell communication and cell cycle in dormancy release (Arora et al 2003;Pang et al 2007;Rohde and Bhalerao 2007). Few large-scale transcription proWling studies, using EST collections and microarrays, may shed light on additional candidate proteins and pathways that might be involved in the regulation and execution of bud dormancy release such as Lea proteins, GTP-binding proteins, Xavonoid biosynthesis and auxin signaling (Pacey-Miller et al 2003;Horvath et al 2005Horvath et al , 2006Keilin et al 2007;Mazzitelli et al 2007;Ruttink et al 2007). Further studies with well deWned experimental systems are needed for the identiWcation of the core cellular processes that are connected with dormancy release.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, genes with predicted roles in DNA synthesis, protein synthesis, and cell cycle are used as molecular markers for axillary bud activity (Stafstrom and Sussex, 1992;Devitt and Stafstrom, 1995;Shimizu and Mori, 1998). A large number of genes associated with the end of dormancy have been identified in grape (Vitis vinifera) by using microarray techniques (Pacey-Miller et al, 2003). Although the expression of dormancy-or outgrowthassociated genes has been characterized, the regulatory mechanisms by which gene expression is linked to developmental phases are still unknown.…”
mentioning
confidence: 99%
“…Bud break is associated to free radical removal through the activation of peroxide scavenging systems such as catalase, ascorbate peroxidase, superoxide dismutase and glutathione reductase (Pacey Miller et al, 2003;Mazzitelli et al, 2007), when oxidative damages are more probable. (Ingram & Barteles, 1996).…”
Section: Proteins Related To Stress or Protection Responses And Detoxmentioning
confidence: 99%
“…Renaut et al (2004) found that deactivation of reactive oxygen species and accumulation of dehydrins were some of the most prominent changes in the transcriptomic profile of poplar trees during seasonal chilling. Bud break is associated to free radical removal through the activation of peroxide scavenging systems such as catalase, ascorbate peroxidase, superoxide dismutase and glutathione reductase (Pacey Miller et al, 2003;Mazzitelli et al, 2007), when oxidative damages are more probable.…”
Section: Genes Involved In Sugar Metabolism and Carbohydrate Catabolismmentioning
confidence: 99%